2012
DOI: 10.1021/cs300290j
|View full text |Cite
|
Sign up to set email alerts
|

Enantiocontrol with a Hydrogen-bond Directing Pyrrolidinylsilanol Catalyst

Abstract: Dichloromethane (DCM), hexane, ethyl acetate (EtOAc), and diethyl ether (Et 2 O) were obtained from EMD Chemicals. Toluene (PhMe), methanol (MeOH), and tetrahydrofuran (THF) were obtained from Fisher Scientific. Palladium on carbon (5 wt% and 10 wt%), anhydrous magnesium sulfate, (-)-sparteine, acetaldehyde, and 2-mesitylmagnesium bromide solution (1.0 M in Et 2 O) were acquired from Sigma Aldrich. Dimethoxyethane, trichlorosilane, secbutyllithium (1.3 M in cyclohexane/hexanes (98/2)), and ytterbium (III) trif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Compound (S)-2·HClO 4 crystallized in the monoclinic crystal system, space group P2 1 , as colorless plates ( Figure 4 and Table 1). The asymmetric unit of compound (S)-2·HClO 4 Figures 2 and 4). The C-Si-C angles are in both independent molecules very close to the ideal tetrahedral angle (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compound (S)-2·HClO 4 crystallized in the monoclinic crystal system, space group P2 1 , as colorless plates ( Figure 4 and Table 1). The asymmetric unit of compound (S)-2·HClO 4 Figures 2 and 4). The C-Si-C angles are in both independent molecules very close to the ideal tetrahedral angle (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The perchlorate salts (S)-1·HClO 4 and (S)-2·HClO 4 were prepared by treatment of (S)-1·HCl and (S)-2·HCl, respectively, with excess perchloric acid (60 wt %). Colorless single-crystals were formed overnight under normal atmosphere at room temperature within the remaining solvent.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group and others have demonstrated that activity of organic, silanol‐containing hydrogen‐bond donor (HBD) catalysts can be tuned by silanol arrangement and acidity (e.g. 4 – 6 , Figure ) . Silanols display higher acidities compared with alcohols, which is attributed to hyperconjugation effects between the oxygen and silicon .…”
Section: Introductionmentioning
confidence: 99%